Typology of Malay Traditional Building Construction Case Study: Bawi Malay House In Kampung Empat Balai, Kampar - Indra Kuswoyo; Yohannes Firzal; Pedia Aldy; Raden Lisa Suryani; Morian Saspriatnadi; Muhd. Arief Al Husaini (UNIVERSITAS PAKUAN, 2023)
Kampung Empat Balai is one of the old villages in Kuok District, Kampar Regency. The kampung comprises traditional Malay houses as cultural heritages that urge to preserve. The house has a unique roof shape and carvings pattern. However, the house is endangering due to a lack of maintenance. This research has aimed to identify the construction of houses that belong to the Bawi ethnic group people. A qualitative descriptive approach has been carried out to investigate and analyse this Malay house. This research found that the Bawi's house has a curving roof type which is known as part of the Lotiok roof type. This stilt house has a structural system in the form of a series of line elements with non-rigid joints that bind each other using notches and pegs as a connection system that is anticipated for earthquakes. Materially, this Bawi'House uses wooden-based materials throughout its construction systems, such as floors, walls, columns, girder beams and roof trusses.Malay house; traditional construction; lontiok roof; wooden-based materials